Tourism Governance with Culinary Cognitive Images Base in the City of Pare-Pare - Nur Salam (Publik : (Jurnal Ilmu Administrasi), 2021)
Culinary tourism is a new thing in the repertoire of interesting and distinctive dishes and tourism. The food is in the form of food that is usually eaten and processed by local residents, and is not consumed outside the area. The purpose of this Reseach to know the tourism governance with culinary cognitive images based in the City of Pare-Pare. The population in this study is tourists Parepare City Destination.  The sample was taken as many as 100 respondents from tourist Parepare City Destination.  The analytical tool in this research is Descriptive Analysis, Instrument Test, Multiple Regression  Analysis,  Significance  Test  (t  test),  and Model Accuracy Test.  The results showed that cognitive  Culinary   image  has  a  significant  positive effect on the interest of tourists visit Parepare City Destination,  and affective Culinary image have  a  significant  positive  effect  on  the  interest  of  tourist visit Parepare City Destination. Both variables are also influential together on the interest of tourists visit Parepare City Destination. Based on the result of this research,  the  management  of  Parepare City Destination can  increase  the  interest  of  tourist  visit  by  increasing  the cognitive Culinary  image variable and the affective Culinary  image variable, because the increasing of both variables is increasing the tourist visit.